The Hegemony and metaphilosophy: Critiquing Western universality through Non-Western thought - Utomo, Alnino; Stephanus Djunatan (Hanifiya: Jurnal Studi Agama-Agama, 2025)
This study critically examines how Western philosophy constructs epistemic hegemony through historical, methodological, and terminological mechanisms, and explores how non-Western traditions such as Confucianism and Daoism can be recognized as complete and authentic without undergoing conceptual subordination. This research is significant as the discourse of global philosophy remains dominated by Western epistemic structures that limit the plurality of rational forms. Employing a qualitative, literature-based approach, this study analyzes key metaphilosophical texts, Jacques Derrida’s theory of deconstruction, and Alain Badiou’s ontology as conceptual tools to trace power relations embedded in the definitions and boundaries of philosophy. The findings reveal that Western philosophy has institutionalized a linear historical narrative, logical-deductive methodological standards, and a Greek-Latin vocabulary as prerequisites for philosophical validity—resulting in the systematic exclusion of non-Western thought. The study further proposes a conceptual framework of dialogical exclusive multiplicity as an alternative for recognizing truth procedures in non-Western traditions as autonomous and equal. The implications of this research open avenues for deconstructing philosophy as the sole legitimate mode of thinking and promote the formation of a more epistemically just global philosophical ecosystem. The originality of this study lies in its critical synthesis of metaphilosophy, deconstruction, and contemporary ontology to construct an alternative paradigm for cross-traditional philosophical inquiry—one based not on inclusion, but on recognition and articulative equality.